2019
DOI: 10.7150/jca.32167
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide-induced Apoptosis of Acute Myeloid Leukemia Cells via NR4A1 Translocation into Mitochondria and Bcl-2 Transformation

Abstract: OBJECTIVE: Fenretinide is reported to induce NR4A1-associated apoptosis in several types of cancer cells. However, it remains unclear about its specific role and the underlying mechanism in acute myeloid leukemia (AML). Therefore, this study aimed to explore the role and mechanism of fenretinide-induced apoptosis in AML.METHOD: Firstly, the NR4A1 mRNA level in the newly diagnosed AML patients was measured, then AML cells were treated with fenretinide at various time points and doses, and cell viability was inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
(39 reference statements)
1
6
0
Order By: Relevance
“…To further investigate the mechanisms underlying hUCMSCs effects on the apoptosis of TICs, we next evaluated the function of the orphan nuclear receptor, NR4A1. Numerous studies have been studied on NR4A1, mostly present in the nucleus in normal condition, can transfer to the mitochondria when membrane permeabilization and cell apoptosis [39]. In our study, NR4A1 is expressed in TICs during proestrus of rats according to our immunohistochemical results demonstrating NR4A1 in the ovaries and immunofluorescence results of NR4A1 in the nucleus of TICs.…”
Section: Discussionsupporting
confidence: 56%
“…To further investigate the mechanisms underlying hUCMSCs effects on the apoptosis of TICs, we next evaluated the function of the orphan nuclear receptor, NR4A1. Numerous studies have been studied on NR4A1, mostly present in the nucleus in normal condition, can transfer to the mitochondria when membrane permeabilization and cell apoptosis [39]. In our study, NR4A1 is expressed in TICs during proestrus of rats according to our immunohistochemical results demonstrating NR4A1 in the ovaries and immunofluorescence results of NR4A1 in the nucleus of TICs.…”
Section: Discussionsupporting
confidence: 56%
“…Wu and coworkers first identified cytosporone b (Csn-B) as an NR4A1 ligand (Fig. 6); however, Csn-B also induced apoptosis in cancer cells via nuclear export of the receptor to the mitochondria, and this was also observed for THPN (55,56,132). Several Csn-B analogues also bound NR4A1 with K D values in the low micromolar range and not only induced mitochondrial localization of NR4A1 but also acted within the nucleus to repress expression of brain and reproductive organexpressed protein (BRE) in gastric cancer cells (56).…”
Section: Nuclear Functions Of Nr4as and Their Ligandsmentioning
confidence: 99%
“…A recent study showed that DHE also targeted super enhancers of pro-oncogenic factors in leukemia, and this includes MYC and results in decreased H3K27 acetylation, thus providing a novel pathway for modulation of MYC expression in leukemia (54). Fenritinimide also induced expression of NR4A1 in AML cells, and this was accompanied by nuclear export of NR4A1, interaction with bcl-2 resulting in induction of apoptosis (55). This pathway is similar to that observed in solid tumor-derived cancer cells and will be further discussed in a subsequent section of the review.…”
Section: Drug/ligand-induced Responsesmentioning
confidence: 99%
“…Fenretinide treatment induces cell death through the following mechanisms: apoptosis (increased cleavage of caspases and PARP proteins; induction of NR4A1 expression, which interacts with Bcl-2, exposing aBH3 domain and a pro-apoptotic function; and induction of ATF3 expression, ATF4 expression, and NOXA transcription) ( 9 , 11 14 , 16 , 18 , 43 ); autophagy (increased LC3-II levels) ( 9 ); endoplasmic reticulum stress and accumulation of reactive oxygen species (ROS) ( 11 , 14 , 16 18 , 43 ); repression of mammalian target of rapamycin (mTOR) signaling and a subsequent reduction in Erk1/2 activity ( 9 ); ceramide production ( 9 , 17 ); antitumor activity against CSCs (reduced CD44, ALDH, Nanog, Sox2, and POU5F1 expression) ( 10 , 16 , 18 ); induction of cell cycle arrest (decreased p-AURA, CDC25, cyclin E2, and cyclin A2 levels and increased p16 levels) ( 9 , 11 , 12 , 18 ); and p38-MAPK signaling ( 19 ) ( Figure 3 ). Several articles have shown that fenretinide preferentially targets CSCs when sphere formation and stemness markers are analyzed ( 9 11 , 14 16 ).…”
Section: Fenretinidementioning
confidence: 99%